2023
DOI: 10.3390/jcm12082774
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of the Rank of Torque Control during Incisor Retraction and Its Impact on the Resorption of Maxillary Central Incisor Roots According to Incisive Canal Anatomy—Systematic Review

Abstract: Background: Root resorption is one of the complications of orthodontic treatment, and has a varied and unclear aetiology. Objective: To evaluate the relationship between upper incisor resorption and contact with the incisive canal and the risk of resorption during orthodontic treatment associated with upper incisor retraction and torque control. Search methods: According to PRISMA guidelines, the main research question was defined in PICO. Scientific databases MEDLINE, EMBASE and the Cochrane Central Register … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The use of maximum anchorage after premolar extraction and incisor retraction can significantly improve lip position, facial profile, and occlusion [ 22 ]. A large range of incisor displacement, unfortunately, comes with a high-risk of exceeding the so-called bone envelope, causing contact between the incisor roots and the palatal plate, the lamina compacta of the incisive canal, which may result in resorption of the incisor roots or fenestrations of the palatal plate [ 23 , 24 ]. Many factors, such as the amount of orthodontic force applied, the speed of tooth movement, the type of orthodontic movement—uncontrolled inclination, controlled inclination, or axial shift—as well as the patient’s age, influence bone remodeling [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of maximum anchorage after premolar extraction and incisor retraction can significantly improve lip position, facial profile, and occlusion [ 22 ]. A large range of incisor displacement, unfortunately, comes with a high-risk of exceeding the so-called bone envelope, causing contact between the incisor roots and the palatal plate, the lamina compacta of the incisive canal, which may result in resorption of the incisor roots or fenestrations of the palatal plate [ 23 , 24 ]. Many factors, such as the amount of orthodontic force applied, the speed of tooth movement, the type of orthodontic movement—uncontrolled inclination, controlled inclination, or axial shift—as well as the patient’s age, influence bone remodeling [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The palatal cortical lamina should be treated as an intact wall that limits the range of planned movement of the incisors. An additional limitation is the lamina compacta, which surrounds the incisive canal and may be the first to get in the way of the incisors during retraction and may also cause their resorption [ 23 , 24 ]. Advanced incisor protrusion should be treated as early as possible in the adolescent growth period when the body’s ability to remodel is high and when orthodontic movement occurs together with the bone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the aforementioned excessive orthodontic forces, the various contributing factors include genetic predisposition, duration of orthodontic treatment, extent of tooth displacement, and the nature of the force applied, whether continuous or intermittent [8][9][10][11][12][13]. Additionally, root resorption may occur due to contact with the lamina dura related to the alveolar process or the incisive canal [9,[14][15][16]. Notably, Kaley and Philips demonstrated a twentyfold increase in the risk of root resorption of the upper incisors due to cortical plate contact [9].…”
Section: Introductionmentioning
confidence: 99%
“…Since all these manipulations occur in the anterior segment of the maxilla, the anatomy of this area is of key importance in the diagnosis and planning of orthodontic movements that will not violate the bone envelope of this section and will not lead to the direct contact of the maxillary incisor roots with the palatal/vestibular cortical bone or the cortical bone of the incisive canal. Previous studies by other authors have shown that such contact may cause complications such as incisor root resorption, and dehiscence and/or fenestration [1][2][3][4][5][6]. A systematic review found that the risk of incisor root resorption is increased by root contact with the incisive canal [5].…”
Section: Introductionmentioning
confidence: 99%